Child‐ and parent‐reported quality of life trajectories in children with epilepsy: A prospective cohort study. (9th May 2017) - Ferro, Mark A.; Avery, Lisa; Fayed, Nora; Streiner, David L.; Cunningham, Charles E.; Boyle, Michael H.; Lach, Lucyna; Glidden, Gina; Rosenbaum, Peter L.; Ronen, Gabriel M.; ,
Summary: Objective: To describe the developmental trajectories of quality of life (QoL) in a large cohort of children with epilepsy, and to assess the relative contribution of clinical, psychosocial, and sociodemographic variables on QoL trajectories. Methods: Five assessments during a 28‐month prospective cohort study were used to model trajectories of QoL. Participants were recruited with their parents from six Canadian tertiary centers. A convenience sample of 506 children aged 8–14 years with epilepsy and without intellectual disability or autism spectrum disorder were enrolled. A total of 894 children were eligible and 330 refused participation. Participating children were, on average, 11.4 years of age, and 49% were female. Nearly one third (32%) had partial seizures. At baseline, 479 and 503 child‐ and parent‐reported questionnaires were completed. In total, 354 children (74%) and 366 parents (73%) completed the 28‐month follow‐up. QoL was measured using the child‐ and parent‐reported version of the Childhood Epilepsy QoL scale (CHEQOL‐25). Results: Child‐reported QoL was fitted best by a six‐class model and parent‐reported QoL by a five‐class model. In both models, trajectories remained either stable or improved over 28 months. Of these children, 62% rated their QoL as high or moderately high, defined as at least one standard deviation above the average CHEQOL‐25 score. Greater family, classmate, and peer social support, fewer symptoms of child and parent depression, and higher receptive vocabulary were identified as the most robust predictors of better QoL (all p < 0.001). Significance: Most children with epilepsy and their parents reported relatively good QoL in this first joint self‐ and proxy‐reported trajectory study. Findings confirm the heterogeneous QoL outcomes for children with epilepsy and the primary importance of psychosocial factors rather than seizure and AED‐specific factors in influencing QoL. These predictors that are potentially amenable to change should now be the focus of specific intervention studies.